Analytical advances in quantum and celestial mechanics : separating rapid and slow subsystems - Oks, E. A. (Evgeniĭ Aleksandrovich) (IOP ebooks. 2020 collection., 2020)
This book is devoted primarily to recent advances in applying the approximate analytical method of the separation of rapid and slow subsystems to other quantum realms. Such systems include hydrogen atoms in a high-frequency laser field, rotator-dipoles in a high-frequency field, one-electron Rydberg quasimolecules in various fields, muonic-electronic helium atoms and the dynamical Stark broadening of spectral lines by plasma ions and electrons. The book also presents novel applications to some unrestricted three-body systems in celestial mechanics, such as a planet orbiting around a binary star or a star-planet-moon system. These results are practically important in the quest for achieving controlled nuclear fusion on Earth, as well as expanding practical applications of lasers and other related fields.